CONTRIBUTO ALLA CONOSCENZA DELLO GNATOSOMA DEGLI ERIOFIDI (ACARIN1, ERIOPHYOIDEA) - Nuzzaci, Giorgio (Entomologica, 2016)
CONTRIBUTION TO THE KNOWLEDGE OF THE GNATHOSOMA OF ERIOPHYID MITES (Acarina: Eriophyoidea) This study was accomplished by preparation and observation of transverse sections of the gnathosoma from specimens of three distinct .species, belonging to two families (Phytoptidae and Diptiliomiopidae) of Eriophyoidea and having very diverse structural characteristics. The species represented in this study are: Phytoptus avellanae Nalepa, Trisetacus iuniperinus (Nalepa), and Diptacus hederiphagus Nuzzaci. The aspects that have been considered in particular are: l. Origin, morphology and connections of the stylets relative to other parts of the gnathosoma, to enable a satisfactory clarifìcation of the mechanism by which Eriophyids penetrate their stylets into plant tissues; 2. Origin, morphology and connections of the ducts of glands associateci with the gnathosoma of Eriophyids. In ali of the species studied, there are 9 individuai stylets, and the origins and connections of them were ascertained. The labrum, an unpaired stylet, appears to have a unique structure: it has a deep longitudinal channel ventrally, and can be more or less elongate relative to the other stylets . Distally, the chelicerae each give rise to two stylets of which the dorsal on e is more sclerotized and substantial; in the basai artide of the chelicera are individuai bundles of tendons and nerve endings; on this basis I consider the respective stylets as the digitus fixus (fìxed digit) and digitus mobilis (movable digit). The movement of the chelicerai stylets is directly linked with a structure peculiar to this group of mites, the motivator; the ultrastructure of this piece has been studied. Lo studio è stato effettuato su sezioni trasversali dello gnatosoma di tre specie distinte appartenenti a due famiglie (Phytoptidae e Diptiliomiopidae) con caratteristiche morfologiche molto diverse a tal riguardo. Le s-pecie utilizzate in questo studio sono: Phytoptus avellanae Nal., Trisetacus juniperinus (Nal.) e Diptacus hederiphagus Nuzzaci. Gli aspetti ...